Various object detection algorithms and their comparison - Mishra, Debani Prasad; Rout, Kshirod Kumar; Mishra, Sivkumar; Salkuti, Surender Reddy (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This paper presents a detailed and comparative analysis of various object detection algorithms. The challenge of object detection is taken care of while studying various algorithms. Throughout the year various methods have been discovered in this field, each having its advantages and drawbacks. This paper aims at providing the systematic study of all the popular algorithms including the conventional ones. Although many methods and techniques come up each year and each of them having superiority other the previous models but at the same time even complexity increases. In this paper, some famous and basic methods of object detection and tracking are discussed. Using these developed techniques good results can be obtained and also the comparison of the efficiency of all the models can be done. Real-time applications and the outcomes are also discussed.